Caring for Patients With Opioid Use Disorder: What Clinicians Should Know About Comorbid Medical Conditions. Issue 1 (5th December 2018) - Slawek, Deepika E.; Lu, Tiffany Y.; Hayes, Benjamin; Fox, Aaron D.
Abstract : Opioid use disorder (OUD) is a growing problem, with opioid‐involved overdose deaths quadrupling since 1999 in the United States. This article reviews comorbid medical conditions related to OUD, starting with complications of behaviors associated with opioid use (e.g., injection drug use), followed by conditions stemming from the direct effects of opioids (e.g., hypogonadism). HIV and hepatitis C virus (HCV) are common infections in people with OUD, and treatment for these conditions can be safely provided regardless of ongoing substance use. Complications of drug injection, such as HIV, HCV, skin and soft tissue infections, and infective endocarditis, may be prevented through provision of sterile syringes and supervised injection facilities. Rare, life‐threatening bacterial infections may present with signs and symptoms that mimic intoxication, such as malaise or stupor, and should be assessed in patients with fever or positive blood cultures. In addition, chronic opioid exposure can lead to hypogonadism, opioid‐induced hyperalgesia, sleep‐disordered breathing, and potentially increased risk of cardiovascular disease and neurocognitive impairment. Pharmacotherapies for OUD (buprenorphine, methadone, and naltrexone) are safe and effective and their adverse opioid effects can be managed in clinical practice. Awareness of OUD‐associated medical conditions and their treatments is an important step in improving the health and wellness of people with OUD.